2010
DOI: 10.1126/scisignal.3139re6
|View full text |Cite
|
Sign up to set email alerts
|

ABL Tyrosine Kinases: Evolution of Function, Regulation, and Specificity

Abstract: ABL-family proteins comprise one of the best conserved branches of the tyrosine kinases. Each ABL protein contains an SH3-SH2-TK (Src homology 3-Src homology 2-tyrosine kinase) domain cassette, which confers autoregulated kinase activity and is common among nonreceptor tyrosine kinases. This cassette is coupled to an actin-binding and -bundling domain, which makes ABL proteins capable of connecting phosphoregulation with actin-filament reorganization. Two vertebrate paralogs, ABL1 and ABL2, have evolved to per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
339
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 312 publications
(353 citation statements)
references
References 239 publications
(273 reference statements)
13
339
0
1
Order By: Relevance
“…The only minor difference we observed was a slightly slower uptake in the dsDNA substrate balanced out by the faster clearance of the joint molecules, and resulting in the same rate and extent of the nicked circular product formation as the wild-type protein. These data are consistent with a sequential phosphorylation of RAD51 proposed earlier (55,56). According this this model, c-Abl phosphorylates RAD51 on Y315 by binding the consensus PXXP motif through its SH3 domain.…”
Section: Discussionsupporting
confidence: 79%
“…The only minor difference we observed was a slightly slower uptake in the dsDNA substrate balanced out by the faster clearance of the joint molecules, and resulting in the same rate and extent of the nicked circular product formation as the wild-type protein. These data are consistent with a sequential phosphorylation of RAD51 proposed earlier (55,56). According this this model, c-Abl phosphorylates RAD51 on Y315 by binding the consensus PXXP motif through its SH3 domain.…”
Section: Discussionsupporting
confidence: 79%
“…In neurons and HEK293 cells, DAB1 enhances the kinase activity of FYN ( 13 ). In an analogy, we found that simultaneous expression of DAB1 and ABL1b, the major splice variant of ABL1 ( 11,12 ), increased the level of Tyr-phosphorylated ABL1b (pY-ABL1b) in a dose-dependent manner in RKO cells ( Fig. 3D ; compare lanes 4-6).…”
Section: Research Articlementioning
confidence: 58%
“…5H, lanes 2 and 4), but not Y2562F or Y2757F (lanes 3 and 5), markedly reduced the pY levels in the colorectal cancer cells. Notably, the aa sequence adjoining TRIO Y2681 has a strong similarity to the ABL target site consensus ( 11 ). It is also known that dTRIO protein binds to dABL ( 15 ).…”
Section: Apc/aesmentioning
confidence: 99%
“…However, it is possible that the Hippo pathway prevents proliferation through other mechanisms as well. Although this study focused on the apoptotic role of c-Abl, c-Abl is also a pro-proliferative factor (reviewed in Sirvent et al 48 and Colicelli 49 ). Activation of c-Abl in the cytoplasm is involved in the response to growth factors [50][51][52] and F-actin assembly.…”
Section: Discussionmentioning
confidence: 99%